(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In present paper the problem of efficiency evaluation of technical system by measurable structural design parameters is investigated. To accomplish the purpose of considered problem it is constructed the mathematical model in the form of a finite-dimensional operator equation, where desired elements are both influence weights of the calculated structural design parameters and technical effectiveness indicator of the system. First, the constructed model is reduced to the normal system, and then the apparatus of the ill-posed inverse problem theory is used for the reduced problem: a regularizing operator is constructed and an algorithm for finding the regularization parameter is developed.